Autism : The Challengeand Global Autism Public Health (Gaph) Initiative : Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2012)
Autism spectrum disorder (ASD) is a developmental neurological disorder characterized by deficits in social behavior & communication, and a restricted range of activities. ASD transcends social, cultural & geographic boundaries. At least 1 in 150 individuals are affected with autism. In Bangladesh there has been a dramatic increase in the visible number of children with Autism. It is estimated by the Ministry of Social welfare that the total number could be as high as 1.4 million, of whom only a few hundred have been diagnosed. Another estimation is that 1 in every 500 children in Bangladesh has Autism, meaning that the approximate number of children with Autism Spectrum Disorder (ASD) in Bangladesh is no less than 280,000. Autism symptoms range from mild to severe. Some individuals have strong intellectual & languagd abilities, whereas others require lifelong care. Many suffers from medical  problems along with autism. The American Academy of Pediatrics (composed of over 60,000 pediatrician) has recommended mandatory autism screening for all children between 18 and 24 months of age because there is compelling evidence that early intervention can result in significant gains in language and cognitive and impact long term outcome. A major barrier to improve the health & wellbeing of children and families touched by autism is the lack of knowledge and expertise. This limits access to care & early intervention and impedes the development of appropriate public health programs that can improve the quality of life for individuals with ASD & their families. These challenges are further complicated by a shortage of experts & trained professionals.JCMCTA 2012; 23(1): 2-6